Émile Jaques-Dalcroze e a educação musical nas dissertações dos programas de pós-graduação em música - Cunha, Karoline de Almeida (2021)
The present work approaches the Émile Jaques-Dalcroze Method in the context of musical education. Focusing on its applicability, we seek to know if, and how, this method presents itself in Brazilian education. The research is bibliographical, and established its theoretical support in some of Émile Jaques-Dalcroze's interlocutors, such as Madureira (2008), Gainza (1964), Berchtold (1965), Mateiro and Ilari (2011); and in the writings of Jaques-Dalcroze himself (1964, 1945, 1930, 1917, 1920) in order to establish theoretical networks on the methodology for Dalcrozian music education. Using a qualitative approach, we took as material for analysis, theses and dissertations that were raised through CAPES (Portal of the Coordination for the Improvement of Higher Education Personnel) with the intention of recognizing academic publications that propose and/or thematize the thoughts and practices of the educator Émile Jaques-Dalcroze musical in the Brazilian academic scene. Based on the objectives, methodologies, theoretical foundations and conclusions identified in reading the material collected, it was possible to obtain data that were interpreted through the technique of content analysis. The research points to the notorious relevance and contributions that the methodological proposals for musical education by Émile Jaques-Dalcroze can offer to the Brazilian musical education. Bringing this theme to light can provide reflections on the paths that Brazilian musical education has been taking, and also those it can take. In this sense, the steps formulated for research consist of: bibliographic survey; deepening the thoughts and concepts of the chosen author; survey of dissertations and theses within the suggested theme; and data analysis.